Drug Interaction between Sirolimus and Ranolazine in a Kidney Transplant Patient. (2nd January 2014) - Masters, Joanna C.; Shah, Mita M.; Feist, Ashley A.
Abstract : Purpose . The case of a kidney transplant recipient who experienced a probable drug interaction between sirolimus and ranolazine is reported. Summary . The narrow therapeutic window of immunosuppressive therapy in transplant recipients requires close monitoring for potential drug-drug interactions. The patient, a 57-year-old Caucasian male kidney transplant recipient, was stable for years on sirolimus as his primary immunosuppressive agent and had a history of chronic angina, for which he was prescribed ranolazine. Upon addition and dose escalation of ranolazine, whole blood sirolimus levels more than tripled, rising to immeasurably high concentrations. After holding sirolimus on multiple occasions and reducing dosage more than 50%, blood levels returned to therapeutic range, while continuing ranolazine. Conclusion . Since ranolazine is a documented P-GP and CYP3A inhibitor, and sirolimus a known substrate for both pathways, it is proposed that ranolazine inhibition of P-GP and CYP3A4 contributed to the significant elevation in sirolimus exposure. No alternative causes for the rise in sirolimus exposure were found, and assessment with the Drug Interaction Probability Scale finds this interaction to be probable. Clinicians should be aware of the potential for this interaction to cause elevated sirolimus exposure and subsequent increase in clinical effect or toxicity, in this case overimmunosuppression.